Penerapan Model TGT Berbantuan Media GAULL (Game Edukasi Wordwall) untuk Mempengaruhi Hasil Belajar Matematika - Ulin Fatimatuz Zahro; M. Syafruddin Kuryanto; Lovika Ardana Riswari (Universitas Muhammadiyah Metro, 2024)
Mathematics is a core subject in elementary school which is considered difficult for most children. This research is motivated by low mathematics learning outcomes due to the monotonous and conventional learning process. The TGT model is a cooperative learning model so that students are more active. GAULL Media (Wordwall Educational Game) is an interesting technology-based media. So this research aims to determine the effect of implementing the TGT model with the help of GAULL media (Wordwall Educational Game) on the mathematics learning outcomes of class IV students. This research is a pre-experimental quantitative research with a one group pretest posttest design conducted on class IV students at SD 3 Karangbener. The independent variable in this research is the TGT model with GAULL media (Wordwall Educational Game) while the dependent variable is mathematics learning outcomes. The population of this study was all students in class IV of SD 3 Karangbener who also served as a sample of 15 students. The data collection technique in this research uses a test technique in the form of essay questions. Data analysis used the paired sample t test. The results of the paired sample t-test show that the Stg (2-tailed) value is 0.000 < 0.05, so Ho is rejected and Ha is accepted. This means that the application of the TGT model assisted by GAULL media (Wordwall Educational Game) influences the mathematics learning outcomes of class IV students.